Tinjauan Yuridis Dampak Kemitraan Transportasi Online Di Bandar Lampung - Angga Alfian; Akbar Ramadhan Gumas; Nadya Shahnaz Gabriella (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
This research was created to discuss the juridical review of the impact of the proliferation of online transportation partners. Indonesia has experienced an industrial revolution, based on the Big Indonesian Dictionary (KBBI), Industrial Revolution is divided into two words, namely Revolution and Industry. Revolution is change that occurs very quickly, while industry is an effort to carry out production. So in conclusion, the Industrial Revolution is an event that happened very quickly in carrying out production activities which were carried out using technological tools and something produced had added value. The proliferation of online transportation partners is an example of the results of the industrial revolution. There are five important variables to consider when evaluating an ecommerce website: interface, navigation, content, reliability, and technical. An interface is a type of application that connects users and facilitates financial and business transactions for the general public. The user interface provides ease of use for its users. One user interface that is currently popular in Indonesia is Go-Jek, an e-commerce application that makes it easier for users to purchase goods or services, whether transported or not. This research will discuss the impact of Go-Jek according to judicial review.